Strategies for using modified resin-based materials to improve the properties and lifetime of dental restorations - Guimarães, Genine Moreira de Freitas (2024)
The objective of the studies in this thesis was to present different performances to influence the properties of the materials and consequently increase the longevity of these materials. The objective was to circumvent the inherent disadvantages of resin materials related to polymerization shrinkage and stresses generated in the substrates involved, and also to use materials that are resistant to degradation at the adhesive interface. In the first study, the aim was to combine thiourethane in the resin matrix (TU-Oli) or as a silane (TU-sil) and to evaluate the effect of different concentrations of functionalized TiO2 nanotubes and nanoparticles on the kinetics, sorption and solubility, light transmission, polymerization depth, flexural strength and mechanical-dynamic analysis of experimental composite resins. It was found that the presence of TU-Oli in the resin matrix significantly increased the DC and decreased the Rpmax, regardless of the TiO2 nanostructure. In terms of cure depth and light transmission, nanostructures containing 0.3% by weight showed more favorable results than the highest concentration used (0.9%). For the groups functionalized with TU-sil or 3- (trimethoxysilyl)propyl methacrylate (TSMP), flexural strength, polymerization stress, and sorption and solubility, both the functionalizations and the nanostructures did not statistically affect the values compared to the control, although there was a tendency for improvement when the nanostructures were added. For DMA, the Tg was significantly higher for the nanotubes, regardless of functionalization, compared to the control. The second study evaluated the performance of triacrylamides used as 4th generation primers to improve bond strength in caries-affected dentin (CAD). The microcosm biofilm to induce caries in dentin was produced from human saliva mixed with McBain medium (0.2% sucrose) in human dentin for 5 days at 5% CO2 and 37°C. The experimental specimens were divided into healthy dentin (HDS) and caries-affected dentin (CAD). The materials were evaluated for dentin microtensile bond strength (TBS) after 24 hours and 6 months of storage in water at 37°C. Collagen reinforcement was evaluated by hydroxyproline assay (n=5), in situ zymography (n=2), and monomer viscosity (n=3). Multi-acrylamides have the potential to reduce collagen degradation and relatively increase bond strength compared to the monofunctional HEMA monomer.